Nucleic acid sensing and immunity. - Vanpouille-Box, Claire; Galluzzi, Lorenzo (International review of cell and molecular biology, 2019)
'Nucleic Acid Sensing and Immunity - PART B, ' Volume 345 of the International Review of Cell and Molecular Biology series, gives a comprehensive overview of the nucleic acid machinery, from plants to mammalians, along with their regulation. Chapters in this updated volume include Nucleic acids sensing in allergic disorders, Nucleic acids sensing in autoimmune disorders, Nucleic acid sensing in inflammatory disorders, Viral nucleic acid sensing inflammasomes in intestinal host defense, Genome damage sensing leads to tissue homeostasis in Drosophila, Nucleic acids sensing in plants, Nucleic Acid sensing in invertebrates, amongst other topics. Key Features: Provides an accurate, state-of-the-art resource on RNA sensing; Includes the work of a well-known tumor immunologist; Links intestinal host defense and viral nucleic acid sensing; Presents a chapter on the negative regulation of DNA sensing, a timely topic. Readership: Immunologists to tumor immunologists and DNA damage biologists. --